Pesquisa de percepção do consumidor para análise de embalagens de cosméticos capilares - SARAIVA, Leticia Ruani Nunes; VETORI, Rhubia Vaz (217, 2020)
Introdução: O Brasil é o quarto maior consumidor de cosméticos no mundo e o primeiro na américa latina, segundo a Associação Brasileira da Indústria de Higiene Pessoal e Cosméticos (ABIHPEC) e a Euromonitor (2018). Enzz Cosmetics é uma marca nacional de cosméticos capilar e facial que visa o tratamento e reconstrução. Sua chegada no mercado é recente e por isso o interesse em analisar a imagem de suas embalagens perante o público-alvo. Objetivo: Analisar a percepção do consumidor em embalagens de produtos cosméticos ao fazer o comparativo de uma linha de uso profissional e outra de uso pessoal. Material e métodos: Uso de questionário online a respeito de duas embalagens de cosméticos da marca Enzz Cosmetics, sendo uma profissional e outra pessoal. Aplicaram-se metodologias: quantitativa – Método subjetivo/afetivo, com aplicação de escala hedônica e de Likert; e qualitativa – Método descritivo para análise da embalagem. Resultados e Discussão: Após a aplicação da pesquisa e dos dados apurados, obteve-se resultados positivos, a aceitação do público em geral superou a marca de 85% em ambas as linhas. Considerações finais: Para aceitação geral, não houve diferença significativa entre as embalagens. A percepção de qualidade das embalagens obteve pontuações superiores a 75% quanto a “Qualidade boa” e “Qualidade muito alta”. Foi possível observar que as embalagens entregam seu conceito. Os atributos que remetem às embalagens estão correlacionados com as definições da empresa.

Introduction: Brazil is the fourth largest consumer of cosmetics in the world and the first in Latin America, according to the Brazilian Association of the Personal Hygiene and Cosmetics Industry (ABIHPEC) and Euromonitor (2018). Enzz Cosmetics is a national capillary and facial cosmetics brand that aims at treatment and reconstruction. Its arrival in the market is recent and therefore the interest in analyzing the image of its packaging before the target audience. Objective: To analyze consumer perception in packaging of cosmetic products when comparing a line of professional use and another for personal use. Material and methods: Use of an online questionnaire regarding two Enzz Cosmetics cosmetic packaging, one professional and one personal. Methodologies were applied: quantitative - subjective / affective method, with application of hedonic and Likert scale; and qualitative - Descriptive method for analyzing the packaging. Results and Discussion: After the application of the research and the data obtained, positive results were obtained, the acceptance of the general public surpassed the mark of 85% in both lines. In terms of quality, both lines had good scores. The product in general, had its image correctly sent to its use (professional and personal). The word cloud had a frequency present between the words: "clean", "professional", "quality", "practicality" for professional and "travel kit", "practicality", "compact" and "hair" for staff, going according to the concepts preached by the brand. Final considerations: For general acceptance, there was no significant difference between packages. The perception of packaging quality obtained scores above 75% for "Good Quality" and "Very high quality". It was possible to observe that the packages deliver their concept. The attributes that refer to the packaging are correlated with the company's definitions.
Consumer perception research of capillary cosmetics packages professional use versus personal use
Keywords: Materiais de embalagem; Cosméticos; Cabelo; Produção Industrial